Exploring the Informal Economy: Analysis of Unincorporated Enterprises in Jammu & Kashmir, India - Jakhar, Babloo; Kumar, Vijay; Sharma, Sachin; Sharma, Swati (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
This paper aims to present a descriptive analysis of unincorporated non-agricultural enterprises (excluding construction) in the Jammu & Kashmir region, highlighting the unique dynamics of the informal sector in the area. Specifically, it seeks to address key research questions regarding the drivers of growth in this sector, the extent of its divergence from national trends, and its implications for local economic development. Through the use of unit-level data from the National Sample Survey Office (NSSO) for the period 2010-11 and 2015-16, the study provides a descriptive analysis that underscores the rapid growth of such enterprises in Jammu & Kashmir compared to the national level. The findings indicate that unincorporated enterprises in Jammu & Kashmir have grown at a significantly faster rate than the all-India average, driven by factors such as supportive local policies, increased entrepreneurial initiatives, and socio-economic conditions unique to the region. This expansion signifies a trend towards increased self-employment and diversified income sources for the local population. However, the growth of the informal sector in Jammu & Kashmir also reveals that the region's economy is still heavily reliant on this sector, in contrast to the overall contraction of the informal sector across India. This divergence points to a structural transformation gap between the Jammu & Kashmir region and the national economy, which warrants further investigation through policy analysis, sector-specific studies, and socio-economic evaluations to better understand the underlying causes and potential solutions. Understanding this gap is crucial for formulating policies aimed at fostering inclusive and sustainable economic development in the region.